Between Sources and Narrative in a Microhistorical Perspective. Reflections after Reading Pleban i wieś. Historia życia proboszcza tenczyńskiego z początków XVIII wieku. Studium mikrohistoryczne [The Plebanus and the Village. A Life History of Tenczynek’s Parish Priest in the Early Eighteenth Century: A Microhistorical Study] by Krzysztof Zamorski - Kraszewski, Igor (Sensus Historiae, 2025)
The article addresses several topics of importance to historians, inspired by Krzysztof Zamorski’s microhistorical study Pleban i wieś [The Plebanus and the Village]. Based on very detailed and diverse sources, the book allows the reader to get to know (or, to use the Author’s metaphor, “to touch”) the world of the village and parish of Tenczynek near Cracow in the first quarter of the 18th century. Many elements of this world contradict stereotypical ideas about the era and the society of the time, especially rural society. This raises the question of to what extent the microhistory of Tenczynek can be considered an exception, and to what extent it can be considered a type, allowing for synthetic generalizations. Dense exposition of sources also allows for reflection on their correct or distorted publication, on the degree of desired modernisation and the need for careful collation with the manuscripts. The final message of this and other microhistories comes as no surprise to specialists: Old Polish society was characterised by enormous diversity, which Krzysztof Zamorski has managed to fully reveal.